(untitled) (Research, Society and Development, 2021)
The complexity of psoriasis, the poor clinical correlation with other influential aspects and the difficulty of treatments related to it, make it difficult to improve the clinical conditions of several individuals who suffer from the disease. For this reason, it is extremely important to seek to better understand its mechanisms and external factors surrounding the pathology, for a better treatment aid. The objective of the research is to understand the immunological mechanisms of inflammation, as well as to understand how the other factors can influence the cause or worsening of psoriasis in the individual’s body. For its development, electronic searches were carried out in the databases, such as Google Scholar, Pubmed, Scielo and Science Direct. In summary, it is possible to observe the action of several cells of the immune system in inflammation, such as T lymphocytes and signaling cytokines, which are important markers for the disease, interleukin-6, in addition to the reactive protein C which is an acute phase protein , are elevated in the pathophysiological process of the disease. On the other hand, external stimuli and stress, demonstrate a considerable clinical correlation with the development of the pathological condition. Thus, the control of interleukins, especially IL-6, becomes a useful tool in monitoring and improving the pathophysiology of the disease.